The Double Movement Method in the Post-Truth Era: A Critique of Scripturalism and Contextualism - Ira Bariroh; Nurul Huda (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2026)
The post-truth era has transformed the authority of religious knowledge and intensified the polarization of Qur'anic interpretation in digital spaces between excessively literalist and overly contextualist approaches. This study aims to critically examine the epistemological foundations of these two interpretive paradigms, evaluate the relevance of Fazlur Rahman's Double Movement method as a via media, and formulate a philosophically robust methodological reconstruction for the digital age. Employing a qualitative library research design with a philosophical hermeneutic approach and Critical Hermeneutics analysis, this study examines Rahman's primary works alongside contemporary hermeneutical literature. The findings reveal that literalist scripturalism neglects the historical and social context of revelation, whereas radical contextualism tends to relativize the normative meaning of the Qur'an. Fazlur Rahman's Double Movement method offers a mediating alternative by fostering a dialogical engagement between text and context. Nevertheless, the method remains constrained by its assumption of historical objectivity, which overlooks the interpreter's pre-understanding and historical consciousness. This study therefore proposes a reconstruction of the Double Movement method into a dialogical-critical model. The proposed model integrates critical reflection on the digital era, dialogue between the text and the interpreter, and Paul Ricoeur's hermeneutical framework. Accordingly, this reconstructed model is expected to assist contemporary interpreters in addressing digital misinformation while preserving the universal values of the Qur'an.